2020
DOI: 10.1016/j.heliyon.2020.e04421
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Poaceae pollen and Phl p 5 allergen concentrations and the impact of weather variables and air pollutants on their levels in the atmosphere

Abstract: The sensitization to grass pollen is a known problem in European countries. Phl p 5 is an important allergen recognized by the majority of grass sensitized individuals. In this study, we evaluated daily variation in airborne Poaceae pollen and Phl p 5 allergen concentrations to determine whether airborne pollen concentrations alone are sufficient to reflect the actual allergenic potential of the air. The relationships between the mentioned pollen and allergen concentrations and associated environmental variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…In this study, Poaceae pollen concentrations were positively correlated with temperature and sunlight and negatively correlated with relative humidity and precipitation. These results are consistent with the behaviour of pollen release from the anther (Pacini, 2000) and known meteorological effects on atmospheric pollen concentrations (Taylor et al, 2002;Ianovici et al, 2015;Peternel et al, 2006;Ščevková et al, 2020;Green et al, 2004 andStennett &Beggs, 2004). However, our results show that the correlations with relative humidity and precipitation were only significant during the last three months of the study after an intense and prolonged drought in New South Wales, which may have affected the number of extreme Poaceae pollen concentration days observed during the study.…”
Section: Correlation Of Poaceae Pollen With Meteorologysupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, Poaceae pollen concentrations were positively correlated with temperature and sunlight and negatively correlated with relative humidity and precipitation. These results are consistent with the behaviour of pollen release from the anther (Pacini, 2000) and known meteorological effects on atmospheric pollen concentrations (Taylor et al, 2002;Ianovici et al, 2015;Peternel et al, 2006;Ščevková et al, 2020;Green et al, 2004 andStennett &Beggs, 2004). However, our results show that the correlations with relative humidity and precipitation were only significant during the last three months of the study after an intense and prolonged drought in New South Wales, which may have affected the number of extreme Poaceae pollen concentration days observed during the study.…”
Section: Correlation Of Poaceae Pollen With Meteorologysupporting
confidence: 91%
“…3). Previous studies have also observed a reduction in pollen concentration with increasing distances from rural areas, changes in land-use practices and different microclimates that dictate species biodiversity (Ianovici et al, 2015;Peternel et al, 2006;Ščevková et al, 2020).…”
Section: Differences In Poaceae Pollen Concentration Between Richmond...mentioning
confidence: 96%
“…Moreover, pollen grains under extreme conditions could produce more allergens as a response to make sure pollination (Moreno-Grau et al, 2016 ; Plaza et al, 2016a ). In the particular case of grasses, there is a sequence in the PAP depending on the species, and this can be observed in significant differences in seasonal variables such as temperature (Bruffaerts et al, 2018 ; García-Mozo, 2017 ; Ščevková et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This further highlights the difficulty of transferring pollen potency research: trends observed in one taxon in a given location cannot be extrapolated to any other. Further, due to the limited taxonomic resolution of current pollen detection methods for grass (Campbell et al, 2020;Jones et al, 2020), overlapping seasons of cross-reactive species and the presence of more than one major allergen (Lol p 1 and Phl p 5) further confound the conclusions that can be drawn about grass pollen potency (Buters et al, 2015;Jochner et al, 2015;Š čevková et al, 2020). Finally, given the substantial and non-systematic geospatial variation in pollen potency, we also conclude that findings cannot be extrapolated geospatially, nor by climatic region.…”
Section: Variation In Pollen Potencymentioning
confidence: 84%